Obtaining Martensitic Structures during Thixoforming of Hypoeutectic Gray Cast Iron - Lucas Bertolino Ragazzo; Davi Munhoz Benati; Rodolfo Lopez Nadal; Eugênio José Zoqui (Advances in Materials Science and Engineering)
The control of parameters such as liquid fraction, holding time, and cooling rate during thixoforming can help control the final microstructure of the thixoformed part, thus improving its mechanical properties. This study intended to investigate conditions required to obtain martensite in hypoeutectic gray cast iron at 3.1% CE (carbon equivalent) deformed in the semisolid state. Samples heated up to 1130, 1135, and 1145°C (liquid fractions of 10, 30, and 45%) were compressed into platens without any holding time (0 s). If a sample presented a martensitic structure for 0 s holding time, new samples were retested at the same temperature for 30, 60, and 90 s holding times. The die casting process was simulated by allowing the platens to become locked after hot compression. Samples that cooled in the locked platens were submitted to higher cooling rates than samples that cooled with the platens open and presented martensite instead of the conventional ferrite and pearlite. Thus, the factor that had the greatest influence on the formation of martensite was the cooling rate rather than stress. The thixoforming process presented good morphological stability, which is highly desirable for industrial applications.